Coating-by-design: design a high-temperature oxidation and corrosion resistant Zr-doped MCrAlY coating fabricated by magnetron sputtering - Shen Tao; Hui Peng; Anqin Zhang; Hongbo Guo (Applied Surface Science Advances)
Here, we propose a rapid coating design and verification approach via magnetron sputtering, which is first applied to Zr-doped MCrAlY coatings. By utilising the compositional gradient of the as-deposited coatings, ten candidates with varying Zr contents were evaluated. Among them, the coating with 0.15 wt.% Zr exhibited the best oxidation and corrosion resistance. Results show that moderate Zr doping promotes the θ-Al2O3 to α-Al2O3 transformation and delays the β to γ/γ′ phase transition, leading to the formation of a dense and smooth oxide scale. However, EBSD analysis reveals that increasing Zr content coarsens the grain size, and excessive Zr accelerates Al depletion and promotes spinel formation. During oxidation, a semicoherent γ/γ′ to α-Al2O3 interface is formed, whereas in corrosion-tested samples, the β-NiAl to α-Al2O3 interface becomes incoherent, weakening interfacial bonding. Nevertheless, Zr diffusion from the coating into the thermally grown oxide (TGO) forms Zr-rich bands, which significantly inhibit Al outward diffusion. Thermo-Calc simulations indicate that the volume fraction of β-NiAl at 1100 °C (low Al content β-NiAl) is much higher than at 900 °C (high Al content β-NiAl), and that Zr has little effect on the overall phase distribution. Coatings prepared via arc ion plating further confirm that Zr-doped coatings outperform Zr-free ones in cyclic oxidation and corrosion resistance.